Comparative study on open system digestion and microwave assisted digestion methods for metal determination in shrimp sludge compost - Nemati, K.; Bakar, Nor Kartini Abu; Abas, M.R.; Sobhanzadeh, E.; Low, K.H. (2010)
The aim of this work was to evaluate two different digestion methods for the determination of the total concentration of metals (Zn, Cu, Cr, Ni, Pb and Cd) in shrimp sludge compost. The compost made from shrimp aquaculture sludge co-composted with organic materials (peat, crushed bark and manure) was used as an organic growing medium for crop. Open system digestion and microwave assisted digestion procedures were employed in sample preparation. Various combinations and volumes of hydrofluoric, nitric and hydrochloric acids were evaluated for the efficiency of both methods. A certified reference material (CRM 146) was used in the comparison of these two digestion methods. The results revealed a good agreement between both procedures and the certified valued. The best recoveries were found in the range between 95 and 99 for microwave assisted digestion with a mixture of 2ml of HF, 6ml of HNO3 and 2ml of HCl. This procedure was recommended as the method for digestion the compost herein based on the recovery analysis and time taken.